2005
DOI: 10.1111/j.1365-313x.2005.02462.x
|View full text |Cite
|
Sign up to set email alerts
|

Soluble starch synthase I: a major determinant for the synthesis of amylopectin in Arabidopsis thaliana leaves

Abstract: SummaryA minimum of four soluble starch synthase families have been documented in all starch-storing green plants. These activities are involved in amylopectin synthesis and are extremely well conserved throughout the plant kingdom. Mutants or transgenic plants defective for SSII and SSIII isoforms have been previously shown to have a large and specific impact on the synthesis of amylopectin while the function of the SSI type of enzymes has remained elusive. We report here that Arabidopsis mutants, lacking a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
177
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 172 publications
(190 citation statements)
references
References 56 publications
13
177
0
Order By: Relevance
“…This mutant line was shown previously to contain 23% less starch in leaves at the end of the illumination period (Delvallé et al, 2005). The loss-of-function insert in this line was located in the intron of the genomic sequence, but a protein could not be detected.…”
Section: Infection Testmentioning
confidence: 89%
See 2 more Smart Citations
“…This mutant line was shown previously to contain 23% less starch in leaves at the end of the illumination period (Delvallé et al, 2005). The loss-of-function insert in this line was located in the intron of the genomic sequence, but a protein could not be detected.…”
Section: Infection Testmentioning
confidence: 89%
“…In the step for amylose formation, in addition to GBSS1, another gene involved in amylopectin synthesis, SS1, encoding a plastidial enzyme (Delvallé et al, 2005), was also up-regulated. Whereas Delvallé et al (2005) reported that SS1 mRNA levels increased at the onset of the light period, SS1 transcript levels were found by Smith et al (2004) to be almost constant during circadian rhythm.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although these enzymes may have different activities depending on the plant species and tissues, they are all present in starchsynthesising cells. SSI appears to be primarily responsible for the synthesis of short glucan chains, as evidenced from SSI mutants in Arabidopsis [52]. Further investigation of the chain-length specificities of maize endosperm SSI has suggested that SSI prefers the shortest amylopectin chains as substrates [53].…”
Section: Starch Synthases (Sss)mentioning
confidence: 99%
“…Genetic analysis suggests that these isoforms have differing roles in amylopectin synthesis. Starch synthase (SS) I is thought to be responsible for the synthesis of the short external chains of amylopectin (DP6-10; Delvalle et al 2005), whereas SSIIa is responsible for the synthesis of longer chains, from DP12-20. Elimination of this enzyme in barley , wheat (Yamamori et al 2000) and rice (Umemoto et al 2002) leads to a very characteristic phenotype involving reduced amylopectin external chain length, reduced granule gelatinization temperature and reduced starch swelling properties.…”
Section: Starch Biosynthesis and Functionalitymentioning
confidence: 99%